Em busca da emancipação humana: contradições, limites e possibilidades do ensino médio integrado a partir do IFSP – São Carlos - Domingues, Marcelo de Godoy (Universidade Federal de São Carlos, 2025)
The objective of this thesis is to analyze the Integrated High School program of Federal Institutes, starting with the IFSP – São Carlos. Based on historical-dialectical materialism, we sought to identify the contradictions, limits, and possibilities of a school whose principle is to promote comprehensive and omnilateral education, based on work as an educational principle. To this end, we employed both documentary analysis and questionnaires and interviews with students, teachers, and other staff, analyzing them through Critical Discourse Analysis. The conclusions indicate that, although there is a perception that the EMI at this institution develops a certain degree of autonomy and comprehensive education for students, this perception is biased by hegemonic discourses. The problem lies in how the institution develops the notion of work, associating it with capitalist production and, therefore, with the need for professionalization under the interests of capital, distancing itself from work as an educational principle. This generates distorted notions about integration and the construction of autonomy, as they end up integrating vocational areas into a population that should receive a strong general education. In this sense, autonomy – rather than being understood as raising students' ethical and political level, lifting them from passivity to create a new hegemony – is reduced to the possibility of choosing between entering the job market or pursuing university studies, possibilities far removed from a truly comprehensive and omnilateral education. Given this perception, it is clear that urgent changes are needed in this teaching modality if the goal is to pursue a unitary school, aiming to develop specialists and politicians (Gramsci, 2021). Such changes include the end of professional training for young people aged 14 to 18; the use of technical knowledge to enable the relationship between theory and practice in a disinterested manner; and ethical and political training for teachers and staff, so that they develop practices consistent with the institution's political proposals, based on the ideas of Marx and Gramsci. These measures are immediate, since their transformative power will only occur with a unitary school, which considers different starting points but aims for a single, unified end point: the development of leaders.
In search of human emancipation: contradictions, limits and possibilities of integrated high school education from IFSP – São Carlos
Keywords: Ensino Médio Integrado; Institutos Federais; Gramsci; Escola Unitária; Jovens; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; 4. Educação de Qualidade